Prevention of Neointimal Hyperplasia by Local Application of Lentiviral Vectors Encoding Pin1 shRNA in Pluronic F127 - Lv, Lei; Shi, Yaxue; Duan, Rundan; Xie, Hui; Zhang, Jiwei; Liang, Wei; Xue, Guanhua; Zhang, Lan; Huang, Xiaozhong (Current Gene Therapy, 2015)
Inhibition of intimal hyperplasia plays an important role in preventing restenosis. Previously, we reported the provocative role of Pin1 in regulating vascular smooth muscle cell (VSMC) proliferation. Here we intended to identify whether locally delivered lentivirus-mediated siPin1 via pluronic F127 (PF127) could inhibit neointimal formation and further explore the potential mechanisms thereof. In vitro studies revealed that lentivirus-mediated siPin1 dispersed in PF127 suppressed proliferation and induced senescence in VSMCs. Reduction of Pin1 expression resulted in a decrease of phospho-Akt (p-Akt) expression level in VSMCs. Reactivation of Akt phosphorylation overcame the siPin1-mediated senescence. In a rat wire injury model, periadventitial delivery of lentivirus-mediated siPin1 via PF127 produced inhibition of intimal hyperplasia 14 days after injury without evidence for toxicity. Furthermore, the reduction of intimal thickness was associated with a decreased amount of PCNA positive cells, decreased telomerase activity and shortened telomere length. Therefore, these results suggest that PF127 delivery of lentivirus-mediated siPin1 to artery may have a therapeutic potential for the treatment of restenosis.
Keywords: Neointimal hyperplasia